Anti-SARS-Cov-2 S-RBD IgG Formed after BNT162b2 Vaccination Can Bind C1q and Activate Complement - Anas H. A. Abu-Humaidan; Fatima M. Ahmad; Dima Awajan; Raba’a F. Jarrar; Nader Alaridah (Journal of Immunology Research)
Background. The ability of vaccine-induced antibodies to bind C1q could affect pathogen neutralization. In this study, we investigated C1q binding and subsequent complement activation by anti-spike (S) protein receptor-binding domain (RBD) specific antibodies produced following vaccination with either the mRNA vaccine BNT162b2 or the inactivated vaccine BBIBP-CorV. Methods. Serum samples were collected in the period of July 2021-March 2022. Participants’ demographic data, type of vaccine, date of vaccination, as well as adverse effects of the vaccine were recorded. The serum samples were incubated with S protein RBD-coated plates. Levels of human IgG, IgA, IgM, C1q, and mannose-binding lectin (MBL) that were bound to the plate, as well as formed C3d, and C5b-9 were compared between different groups of participants. Results. A total of 151 samples were collected from vaccinated (n=116) and nonvaccinated (n=35) participants. Participants who received either one or two doses of BNT162b2 formed higher levels of anti-RBD IgG and IgA than participants who received BBIBP-CorV. The anti-RBD IgG formed following either vaccine bound C1q, but significantly more C1q binding was observed in participants who received BNT162b2. Subsequently, C5b-9 formation was significantly higher in participants who received BNT162b2, while no significant difference in C5b-9 formation was found between the nonvaccinated and BBIBP-CorV groups. The formation of C5b-9 was strongly correlated to C1q binding and not to MBL binding, additionally, the ratio of formed C5b-9/bound C1q was significantly higher in the BNT162b2 group. Conclusion. Anti-RBD IgG formed following vaccination can bind C1q with subsequent complement activation, and the degree of terminal complement pathway activation differed between vaccines, which could play a role in the protection offered by COVID-19 vaccines. Further investigation into the correlation between vaccine protection and vaccine-induced antibodies’ ability to activate complement is required.